A novel use of biomechanical model‐based deformable image registration (DIR) for assessing colorectal liver metastases ablation outcomes. Issue 10 (18th August 2021) - Anderson, Brian M.; Lin, Yuan‐Mao; Lin, Ethan Y.; Cazoulat, Guillaume; Gupta, Sanjay; Kyle Jones, A.; Odisio, Bruno C.; Brock, Kristy K.
Abstract: Purpose: Colorectal cancer is the third most common form of cancer in the United States, and up to 60% of these patients develop liver metastasis. While hepatic resection is the curative treatment of choice, only 20% of patients are candidates at the time of diagnosis. While percutaneous thermal ablation (PTA) has demonstrated 24%–51% overall 5‐year survival rates, assurance of sufficient ablation margin delivery (5 mm) can be challenging, with current methods of 2D distance measurement not ensuring 3D minimum margin. We hypothesized that biomechanical model‐based deformable image registration (DIR) can reduce spatial uncertainties and differentiate local tumor progression (LTP) patients from LTP‐free patients. Methods: We retrospectively acquired 30 patients (16 LTP and 14 LTP‐free) at our institution who had undergone PTA and had a contrast‐enhanced pre‐treatment and post‐ablation CT scan. Liver, disease, and ablation zone were manually segmented. Biomechanical model‐based DIR between the pre‐treatment and post‐ablation CT mapped the gross tumor volume onto the ablation zone and measured 3D minimum delivered margin (MDM). An in‐house cone‐tracing algorithm determined if progression qualitatively collocated with insufficient 5 mm margin achieved. Results: Mann–Whitney U test showed a significant difference ( p  < 0.01) in MDM from the LTP and LTP‐free groups. A total of 93% (13/14) of patients with LTP had a correlation between progression and missing 5 mm of margin volume. Conclusions: Biomechanical DIR is able to reduce spatial uncertainty and allow measurement of delivered 3D MDM. This minimum margin can help ensure sufficient ablation delivery, and our workflow can provide valuable information in a clinically useful timeframe.